NCSSD-YOLO: a non-causal state space duality-based instance segmentation model for pacific white shrimp - Weiqiang Ni; Chenqing Zhang; Yiqing Zhang; Siyi Li; Haitao Wang; Chenchen Wu; Lin Luo; Qinglang Liang; Zequn Peng; Shenghua Li; Yanqing Chen; Shiyin Chen; et al. (Aquaculture International, 2026)

Wave climate characteristics and long-term trends in the northern South China Sea: A 31-year hindcast study for offshore engineering applications - Jinzong Guan; Qianru Niu; Yanqing Feng; Yan Li; Xiaomei Liao; Lin Mu (Ocean Engineering, 2026)

Isomer-specific fate of 4-nonylphenols in textile dyeing wastewater treatment: Insights from aqueous–sludge mass balance - Lang Liu; Yanqing Zhao; Jianyi Zhang; Yuanyuan Liu; Jingwen Zeng; Shengtao Ma; Meiqing Lin; Xunan Ning (Journal of Water Process Engineering, 2026)

Hierarchical NiSx@Zn0.1Cd0.9S heterostructures with enhanced charge separation for efficient solar-to-hydrogen conversion - Along Gao; Zihui Yan; Xiaoming Liu; Qi Yuan; Sisi Zhan; Yanqing Li; Jun Lin (Fuel, 2026)

Correction: Highly Sensitive “On-off” Fluorescent Probe TPA-DNBS Based on Triphenylamine Derivative for Selective Detection of Cysteine - Siyi Wei; Yanqing Xu; Qian Long; Haotian Xie; Wenqi Wu; Xueke Chen; Yan Lin; Hanfeng Cui (Journal of Fluorescence, 2025)

Seasonal variations in greenhouse gas production in coastal sandy sediments - Hao Zheng; Yanqing Feng; Yanshu Wang; Chenqingfeng Gao; Daochao Xing; Zhengyuan Li; Huizhong He; Qiang Liu; Zhengxin Yin; Xianbiao Lin (Marine Pollution Bulletin, 2025)

Tri-modal fibrous electronic skin enabling thermal sensing, electrophysiological monitoring, and directional moisture transport - Yidong Peng; Xi Lin; Haoran Liu; Jiancheng Dong; Yunpeng Huang; Lailai Qin; Yanqing Gu; Tianxi Liu (Chemical Engineering Journal, 2025)

Highly Sensitive “On-off” Fluorescent Probe TPA-DNBS Based on Triphenylamine Derivative for Selective Detection of Cysteine - Siyi Wei; Yanqing Xu; Qian Long; Haotian Xie; Wenqi Wu; Xueke Chen; Yan Lin; Hanfeng Cui (Journal of Fluorescence, 2025)

Synergistic effects of biochar and E. coli on reducing cadmium bioavailability and improving soil fertility through enhanced bacterial-fungal interactions - Quan Chen; Rongrong Lin; Wan-Rong Zhang; Yafeng Wang; Yanqing Xiong; Pengfei Wang; Yu Huang; Min Wu; Peng Yi; Bo Pan (Journal of Hazardous Materials, 2025)

A novel anti-OX40 human monoclonal antibody that blocks OX40/OX40L signaling and depletes OX40+ T cells - Zhen Li; Lin Liu; Xiaobo Chen; Yanqing Wang; Yuxuan Wang; Yuxiu Zhang; Bingqiang Zhang; Xiao Wu; Muhammad Omer Iqbal; Jin Chen; Yuchao Gu (Marine Life Science & Technology, 2025)
Tumor necrosis factor receptor superfamily member 4 (TNFRSF4), also known as OX40, plays a crucial role in the regulation of T-cell immune responses under normal physiological conditions. Abnormal expression of OX40 and its cognate ligand OX40L (TNFSF4) have been associated with various autoimmune diseases, indicating that blocking the OX40/OX40L pathway could be a promising strategy for the treatment of a broad range of T cell-mediated autoimmune diseases. Here, we screened and characterized a fully human anti-OX40 antibody (JY007) from a naïve human scFv phage library. JY007 has an affinity constant of 7.71 nmol/L and effectively inhibited the OX40-OX40L interaction at both molecular and cellular levels, with IC 50 values of 1.088 and 10.12 nmol/L, respectively. Furthermore, JY007 demonstrated the ability to deplete activated T lymphocytes through antibody-dependent cellular cytotoxicity (ADCC) activity, with an EC 50 of 5.592 pmol/L. The combination of ADCC and its antagonist activity against OX40 suggests potential efficacy in suppressing inflammatory responses mediated by the OX40/OX40L pathway. Additionally, we employed molecular docking, site-directed mutagenesis, and competitive ELISA to pinpoint the epitopes on OX40. The results revealed that JY007 binds to Pro 37 , Ser 38 , and Asp 40 of OX40. Interestingly, we also found that the most potent anti-OX40 antibody drug in the clinical stage, KHK4083, binds to different OX40 amino-acid residues, including Asp 74 , Lys 82 , Asp 117 , Ser 118 , Tyr 119 , and Lys 120 . This divergence suggests that the novel monoclonal antibody JY007 holds promise as a potential therapeutic option for patients with atopic dermatitis and may find broad applications in the treatment of autoimmune diseases.

Chronic exposure to liquid crystal monomer EBCN at environmentally relevant concentrations induces testicular dysfunction via the gut-testis axis - Jun Wu; Daojun Lv; Wanmei Lin; Yiyou Mao; Yanqing Xia; Leilei Feng; Tianxin Zhao; Xiangming Mao; Fangpeng Shu; Haibin Guo (Journal of Hazardous Materials, 2025)

Long-term effectiveness of heavy metal(loid) stabilization: Development of an assessing method - Yanqing Liu; Zewen Wang; Xiao Tan; Deyi Hou; Liping Fang; Aijun Lin; Fangbai Li; Guilan Duan (Environmental Pollution, 2025)

A Deniable Encryption Method for Modulation-Based DNA Storage - Ling Chu; Yanqing Su; Xiangzhen Zan; Wanmin Lin; Xiangyu Yao; Peng Xu; Wenbin Liu (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Mechanism of JNK action in oxidative stress–enhanced gut injury by Clostridium perfringens type A infection - Hailan Lin; Yifan Liu; Ling Zhang; Fan Yang; Yanqing Liu; Yuhang Li; Yuxuan Liu; Zhiyun Qiu; Hongyue Chen; Daoling He; Yan Zhu; Ling Gan (Veterinary Microbiology, 2024)

Combination of biotransformation and metabolomics reveals tolfenpyrad-induced hepatocytotoxicity - Xin Jiang; Yingjie Zhu; Suhe Dong; Runfeng Lin; Peihong Zhu; Jie Mao; Yanqing Cao; Xiaoyao Yin; Fangting Dong; Kun He; Na Wang (Science of The Total Environment, 2024)

Whole-genome sequencing identifies novel genes for autism in Chinese trios - Suhua Chang; Jia Jia Liu; Yilu Zhao; Tao Pang; Xiangyu Zheng; Zhirui Song; Anyi Zhang; Xuping Gao; Lingxue Luo; Yanqing Guo; Jing Liu; Li Yang; et al. (Science China Life Sciences, 2024)

Unveiling the versatile performance of transition metal sulfides in peroxymonosulfate activation - Zhifang Zhao; Lin Lin; Shanshan Liu; Yiqian Chen; Sanford V. Daniels; Zijian Xu; Zhenhua Chen; Haitao Li; Yanqing Wu; Lingling Guo; Qiteng Zheng; Zhenhua Duan; et al. (Chemical Engineering Journal, 2024)

Retraction Note: Coordination evaluation of urban tourism and urban development based on TOPSIS method—a case of Xiamen city - Chunxia Zheng; Yawei Wu; Yanqing Lin; Yawen Zheng (Environmental Science and Pollution Research, 2024)

Strategic small molecule engineering: Unleashing the full potential of Kevlar aramid membrane in organic solvent nanofiltration - Yanqing Xu; Jiaqi Xiong; Qite Qiu; Chenfei Lin; Junbin Liao; Huiming Ruan; Jiangnan Shen (Chemical Engineering Journal, 2024)

New insight into the effects of p-benzoquinone on photocatalytic reduction of Cr(VI) over Fe-doped g-C3N4 - Shi-Wen Lv; Jialu Pan; Xiaoran Wang; Yifan Shao; Yanqing Cong; Lin Che (Environmental Research, 2024)

MicroRNA-194-5p/Heparin-binding EGF-like growth factor signaling mediates dexamethasone-induced activation of pseudorabies virus in rat pheochromocytoma cells - Chen Zhang; Yuxuan Liu; Fan Yang; Yifan Liu; Naixiu Wang; Yuhang Li; Yanqing Liu; Zhiyun Qiu; Lin Zhang; Xiaoyan You; Ling Gan (Veterinary Microbiology, 2024)

Assessment of Crop Yield in China Simulated by Thirteen Global Gridded Crop Models - Dezhen Yin; Fang Li; Yaqiong Lu; Xiaodong Zeng; Zhongda Lin; Yanqing Zhou (Advances in Atmospheric Sciences, 2024)

Air pollution and technological innovation in China: a two-way dynamic perspective - Shoufu Lin; Yanqing Xie; Zhaozhi Wang; Lingyu Zhong; Lian Xiao; Shanyong Wang (Environment, Development and Sustainability, 2024)

Historical variability of cotton yield and response to climate and agronomic management in Xinjiang, China - Yanqing Zhou; Fang Li; Qinchuan Xin; Yaoming Li; Zhongda Lin (Science of The Total Environment, 2024)

Distinct variabilities of soil abundant and rare bacteria relate differently to carbon cycling functionality in eroded ecosystems - Lanlan Du; Shengli Guo; Rui Wang; Yanqing Guo; Yaxian Hu; Lin Yang; Weijia Li (CATENA, 2024)

Connectome architecture modulates the gray matter atrophy in major depression disorder patients with diverse suicidal ideations - Shengli Chen; Xiaojing Zhang; Shiwei Lin; Yingli Zhang; Ziyun Xu; Yanqing Li; Manxi Xu; Gangqiang Hou; Yingwei Qiu (Brain Imaging and Behavior, 2023)

Activation of indigenous denitrifying bacteria and enhanced nitrogen removal via artificial mixing in a drinking water reservoir: Insights into gene abundance, community structure, and co-existence model - Shangye Yang; Tinglin Huang; Haihan Zhang; Honghong Guo; Ruzhu Hu; Zishen Lin; Yanqing Li; Ya Cheng (Environmental Research, 2023)

The microstructure and gel properties of linseed oil and soy protein isolate based-oleogel constructed with highland barley β-glucan and its application in luncheon meat - Yanqing Ma; Fayin Ye; Jia Chen; Jian Ming; Caiqiong Zhou; Guohua Zhao; Lin Lei (Food Hydrocolloids, 2023)

RETRACTED ARTICLE: Coordination evaluation of urban tourism and urban development based on TOPSIS method—a case of Xiamen city - Chunxia Zheng; Yawei Wu; Yanqing Lin; Yawen Zheng (Environmental Science and Pollution Research, 2023)

Hepatocyte steatosis inhibits hepatitis B virus secretion via induction of endoplasmic reticulum stress - Qichuang Liu; Maoyuan Mu; Huan Chen; Guoyuan Zhang; Yanqing Yang; Jun Chu; Ying Li; Fangwan Yang; Shide Lin (Molecular and Cellular Biochemistry, 2022)

Cloning, in silico characterization, subcellular localization, and expression of a heat shock cognate 70 kDa protein/gene (EjHsc70-2) from Eriobotrya japonica - Shoukai Lin; Ti Wu; Ming Li; Xiaoming Huang; Yanqing Zhang; Linxiao Han; Bisha Wu; Yu Chen; Suying Lin; Dahe Lin; Minlan Wu; Jincheng Wu (Acta Physiologiae Plantarum, 2019)

Hypoxia inducible factor (HIF) in the tumor microenvironment: friend or foe? - Yanqing Huang; Daniel Lin; Cullen M. Taniguchi (Science China Life Sciences, 2017)

Changes in runoff and eco-flow in the Dongjiang River of the Pearl River Basin, China - Kairong Lin; Yanqing Lian; Xiaohong Chen; Fan Lu (Frontiers of Earth Science, 2014)